In vitro antioxidant and antibacterial activities of two fresh water Cyanobacterial species, Oscillatoria agardhii and Anabaena sphaerica - Azza M. Abd El-Aty, Amal A. Mohamed, Farag A. Samhan (Journal of Applied Pharmaceutical Science, 2014)
Cyanobacteria are potential sources of biologically active compounds with antiviral, antibacterial, antifungal, and anticancer activities. In the present investigation, the effect of different solvents, including methanol, acetone, and water on the total phenolic, flavonoid, antioxidant and antibacterial activities of Oscillatoria agardhii and Anabaena sphaerica extracts were evaluated. The results showed that solvents with different polarities have various effects on phenolic content and antioxidant activity. Among the tested solvents, methanolic extract of Oscillatoria agardhii showed the highest antioxidant activity as well as the highest phenolic content. Organic extracts (with methanol or acetone) of the tested species actively inhibited the growth of bacteria compared to aqueous extracts. The highest antibacterial activity was detected by acetone extract of Oscillatoria agardhii against Salmonella senftenberg. By GC-MS analysis some important heterocyclic compound were identified in both Oscillatoria agardhii and Anabaena sphaerica crude extracts. This appeared to be responsible for such excellent antioxidant and antibacterial activity together with other unidentified compounds. Further exploration of antibacterial potential of cyanobacteria can open new horizons.
Keywords: Antibacterial activity,cyanobacteria, DPPH radical scavenging assay, phenolic compounds, volatile organic compounds.